Vocabulary learning at primary school: a comparison of EFL and CLIL. Issue 5 (2nd September 2016) - Tragant, Elsa; Marsol, Anna; Serrano, Raquel; Llanes, Àngels
Abstract : Comparative studies in content and language integrated learning (CLIL) often show CLIL students to be at something of an advantage over their non-CLIL peers. However, such studies are often difficult to interpret given problems of cross-group comparability (different schooling systems, different number of instructional hours, bias attributable to selection/self-selection, etc.). This study focuses on a single group of schoolchildren ( n = 22), aged eight years old, that were exposed to English as a foreign language (EFL) instruction in the fall term and to CLIL instruction (Science) in the winter term. The main objectives are to analyze the vocabulary of the class materials and to examine gains in productive lexical knowledge. Our results show that students were exposed to a greater number of words and to more abstract and technical vocabulary in the CLIL materials, but that they made significant progress in vocabulary learning in both contexts. The study also reveals that learning English through Science proved to be a more challenging experience than learning English in the EFL class.